2013
DOI: 10.1080/13854046.2013.767379
|View full text |Cite
|
Sign up to set email alerts
|

Visuoconstructional Abilities in Cognitively Healthy Illiterate Turkish Immigrants: A Quantitative and Qualitative Investigation

Abstract: Assessment of visuospatial function is an integral part of most neuropsychological assessments and is frequently assessed by visuoconstructional tests. A significant impact of limited schooling and illiteracy has been found on numerous neuropsychological tests and it can be difficult to interpret test results from illiterate individuals. In this study, quantitative and qualitative aspects of performance of elderly cognitively healthy illiterate and literate Turkish immigrants were compared on five commonly use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 22 publications
5
29
0
3
Order By: Relevance
“…Western instruments used to assess the domain construction, such as the Clock Drawing Test, led to frustration in multiple studies and had limited usefulness in the clinical practice with low-educated patients. This is in line with the finding by Nielsen and Jorgensen (2013), that even healthy illiterate people may experience problems with graphomotor construction tasks. The Stick Design Test, that does not rely on graphomotor responses, was described as more acceptable for low-educated patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Western instruments used to assess the domain construction, such as the Clock Drawing Test, led to frustration in multiple studies and had limited usefulness in the clinical practice with low-educated patients. This is in line with the finding by Nielsen and Jorgensen (2013), that even healthy illiterate people may experience problems with graphomotor construction tasks. The Stick Design Test, that does not rely on graphomotor responses, was described as more acceptable for low-educated patients.…”
Section: Discussionsupporting
confidence: 92%
“…Over the next decades, a dramatic increase is expected in the number of people living with dementia in developing regions compared to those living in developed regions (Ferri et al, 2005;Prince et al, 2013), due to improvements in life expectancy and rapid population aging, especially in lower-and showed that adaptations are needed to make tests suitable for populations with diverse backgrounds (Richardson, 2003). It is now widely documented that neuropsychological test performance is substantially affected by factors such as culture, language, (quality of) education, and literacy (Ardila, 2005(Ardila, , 2007Ardila, Rosselli, & Rosas, 1989;Nielsen & Jorgensen, 2013;Nielsen & Waldemar, 2016; Ostrosky-Solis, Ardila, Rosselli, Lopez-Arango, & Uriel-Mendoza, 1998;Teng, 2002). The rising number of patients with dementia from low-educated and non-Western populations therefore calls for an increase in studies addressing the reliability, validity, and cross-cultural and cross-linguistic applicability of neuropsychological instruments used to assess dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Among those who tried to draw the cube, the three-dimensional figure became a meaningless juxtaposition of two-dimensional figures and the angles became rounded (data unpublished). There specific findings were corroborated by another study on visuoconstructional abilities among illiterate Turkish immigrants in Denmark [17. Keeping this in mind, we examined the performance of the RUDAS in a population-based setting and being administered by trained lay research workers.…”
Section: Methodssupporting
confidence: 56%
“…However, most of these have not been properly validated in cross‐cultural settings and will often be inappropriate or even misleading in evaluations of ethnic minorities as they are biased by cultural, linguistic, and educational factors . This is especially evident in the case of assessments of elderly migrants with limited education and proficiency in the language of the receiving country . Thus, a significant challenge when assessing patients from ethnic minorities with conventional neuropsychological tests is the unknown validity of the tests in these populations.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] This is especially evident in the case of assessments of elderly migrants with limited education and proficiency in the language of the receiving country. [5][6][7][8] Thus, a significant challenge when assessing patients from ethnic minorities with conventional neuropsychological tests is the unknown validity of the tests in these populations.…”
mentioning
confidence: 99%